MULTICULTURAL SCHOOL MANAGEMENT IN THE DEVELOPMENT OF RELIGIOUS INCLUSIVENESS CULTURE IN SMK BHAKTI KARYA PARIGI WEST JAVA (International Conference on Social and Islamic Studies, 2021)
Education as a sub-culture of society should be able to contribute to building harmony above differences, especially religious differences. One of the efforts that can be taken in this regard is the practice of multicultural school management. The existence of multicultural school management shows that schools officially recognize diversity through policies in order to organize and accept this diversity. Through the implementation of multicultural school management at SMK Bakti Karya Parigi Pangandaran, West Java, it is hoped that education will be able to contribute to developing religious inclusivism in social life. The method used in this research is field research using a qualitative approach. The main subjects in this study were the principal and manager of SMK Bakti Karya Parigi Pangandaran, West Java. This research can be used as a material object is SMK Bakti Karya Parigi and the formal object is Multicultural School Management in the Development of Inclusive Religious Culture. Data collection techniques used participatory observation, interviews, documentation and data triangulation. Meanwhile, the data analysis used Spradley model data analysis technique with domain, taxonomy, componential, cultural and triangulation analysis. The results show that the implementation of multicultural school management at SMK Bakti Karya has included all management functions, from planning, organizing, implementing, and supervising schools and one of the results of the practice of multicultural school management is the development of a religious inclusiveness culture in the school environment and the community. This can be proven by the school's ability to accommodate differences, especially religious differences in the school environment to reach school goals together.